High efficiency solar steam generator comprising sodium alginate-polydopamine hydrogel for photothermal water sanitation. (June 2022) - Chen, Shuni; Ma, Danni; Gao, Wenxiu; Zhou, Sihong; Guo, Yanming; Pan, Qinghui; Shuai, Yong
Highlights: Preparation of degradable Na alginate-polydopamine photothermal distillation hydrogel. The hydrogel has a good porous structure and hydrophilic properties. High absorption for sunlight wavelengths resulted in high evaporation rate. Hydrogel has some antibacterial properties and provides high-quality evaporated water. A design for a water purification device that uses the hydrogel is presented. Abstract: Photothermal distillation is an environmentally friendly water sanitation technology based on solar energy, where clean water is obtained by accelerating water evaporation through solar illumination. In this study, a sodium alginate-polydopamine hydrogel was prepared via a spreading-soaking workflow and used as a thermal evaporator. The hydrogel has well-developed pore channels, absorption above 94% for visible light and the 2.5–4 μm infrared band, an evaporation capacity of 1.40 kg·m −2 ·h −1, as well as good antimicrobial properties. The concentration of total dissolved solids (TDS) in the water purified with this system was approximately 16 ppm, much lower than that of tap water commonly used by families. A design is presented for a photothermal distillation system, based on this hydrogel, that can supply drinking water for domestic use. The study demonstrates the potential of hydrogel thermal evaporators for applications such as seawater desalination and wastewater treatment.